Physical Restraint Use within Maltese Long-Term Care Settings - Maria Aurora, Fenech (Magyar Gerontológia, 2023)
The holistic study looked at the locally unexplored environment, providing a platform of knowledge base and information on physical restraint use. The project secured relevant information focal to the older person residents, health care providers and policy makers within long-term care settings.